Atención al Cliente del Personal Administrativa de la Empresa ESPOIR - Fonseca Villafuerte, Joseline Maoli (2018)
In the city of Babahoyo with what to credits there are several options in that area, where potential customers can make their best choice and that's where ESPOIR Foundation comes in, since it is a company dedicated to microcredit in its group modality. credit also known as communal banking.